2005
DOI: 10.1007/s00259-004-1752-1
|View full text |Cite
|
Sign up to set email alerts
|

90Y microsphere treatment of unresectable liver metastases: changes in 18F-FDG uptake and tumour size on PET/CT

Abstract: The metabolic information obtained from FDG-PET/CT seems to provide a more accurate and earlier assessment of therapy response following 90Y microsphere treatment than does the anatomical CT information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 21 publications
1
27
0
2
Order By: Relevance
“…On the basis of the criteria of the European Organization for Research and Treatment of Cancer (EORTC) PET Study Group, the SUV of the hottest tumor voxel (SUV max ) has traditionally been considered a hallmark of tumor vitality, useful for predicting metabolic response to treatment (24). Indeed, several studies have reported that SUV max is more accurate than tumor size for prediction of outcome after radioembolization for unresectable liver metastases of different origins (6,7,25). However, a consensus group developed PERCIST to overcome certain limitations of the EORTC criteria and thus to serve as an improved framework for 18 F-FDG PET response assessment (15).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the criteria of the European Organization for Research and Treatment of Cancer (EORTC) PET Study Group, the SUV of the hottest tumor voxel (SUV max ) has traditionally been considered a hallmark of tumor vitality, useful for predicting metabolic response to treatment (24). Indeed, several studies have reported that SUV max is more accurate than tumor size for prediction of outcome after radioembolization for unresectable liver metastases of different origins (6,7,25). However, a consensus group developed PERCIST to overcome certain limitations of the EORTC criteria and thus to serve as an improved framework for 18 F-FDG PET response assessment (15).…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding simply underscores the controversies regarding the prognostic value of morphologic tumor response. Although some authors have reported a higher response rate on 18 F-FDG PET than on CT and MRI in patients treated with SIRT (26)(27)(28)(29)(30), the prognostic value of metabolic treatment response assessment has only rarely been evaluated in cases of hepatic metastases. In a preliminary study focusing on cholangiocellular carcinoma (16), we found higher discrimination between SIRT responders and nonresponders for 18 F-FDG PET than for CT or MRI.…”
Section: Discussionmentioning
confidence: 99%
“…In a significant number of cases 'stable disease' could actually be minor, partial, or even complete response. In order to improve sensitivity in assessing tumor response, it is therefore strongly recommended that 18 F-FDG-PET or functional MRI (diffusion-weighted MRI) is added to posttreatment response assessment protocols [56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%